Defense mechanisms promoting tolerance to aggressive Phytophthora species in hybrid poplar - Cerny, Martin; Berka, Miroslav; Dvořák, Miloň; Milenković, Ivan; Saiz-Fernández, Iñigo; Brzobohatý, Břetislav; Ďurkovič, Jaroslav (Frontiers in Plant Science, 2022)
Poplars are among the fastest-growing trees and significant resources in agriculture and forestry. However, rapid growth requires a large water consumption, and irrigation water provides a natural means for pathogen spread. That includes members of Phytophthora spp. that have proven to be a global enemy to forests. With the known adaptability to new hosts, it is only a matter of time for more aggressive Phytophthora species to become a threat to poplar forests and plantations. Here, the effects of artificial inoculation with two different representatives of aggressive species (P. cactorum and P. plurivora) were analyzed in the proteome of the Phytophthora-tolerant hybrid poplar clone T-14 [Populus tremula L. 70 × (Populus × canescens (Ait.) Sm. 23)]. Wood microcore samples were collected at the active necrosis borders to provide insight into the molecular processes underlying the observed tolerance to Phytophthora. The analysis revealed the impact of Phytophthora on poplar primary and secondary metabolism, including carbohydrate-active enzymes, amino acid biosynthesis, phenolic metabolism, and lipid metabolism, all of which were confirmed by consecutive metabolome and lipidome profiling. Modulations of enzymes indicating systemic response were confirmed by the analysis of leaf proteome, and sampling of wood microcores in distal locations revealed proteins with abundance correlating with proximity to the infection, including germin-like proteins, components of proteosynthesis, glutamate carboxypeptidase, and an enzyme that likely promotes anthocyanin stability. Finally, the identified Phytophthora response proteins were compared to those previously found in trees with compromised defense against Phytophthora, namely, Quercus spp. and Castanea sativa. That provided a subset of candidate markers of Phytophthora tolerance, including certain ribosomal proteins, auxin metabolism enzymes, dioxygenases, polyphenol oxidases, trehalose-phosphate synthase, mannose-1-phosphate guanylyltransferase, and rhamnose biosynthetic enzymes. In summary, this analysis provided the first insight into the molecular mechanisms of hybrid poplar defense against Phytophthora and identified prospective targets for improving Phytophthora tolerance in trees.